ANALISIS KANDUNGAN KLORIN BEBAS (Cl2) PADA AIR MINUM DALAM KEMASAN MEGAVIN MENGGUNAKAN MULTIPARAMETER PHOTOMETER - Syahwarani, Nurhaliza; Mona Milenia, Putri (DE FACTO : Journal Of International Multidisciplinary Science, 2025)
This study aims to analyze the concentration of free chlorine (Cl?) in bottled drinking water branded Megavin using a Multiparameter Photometer. Free chlorine is considered an essential parameter of drinking water quality, as it functions as a disinfectant that eliminates pathogenic microorganisms while also serving as an indicator of microbiological safety. Insufficient chlorine levels may reduce disinfection effectiveness, whereas excessive concentrations can pose potential health risks to consumers. Samples were collected from various bottle sizes of Megavin available on the market and were analyzed using a photometric method in accordance with standardized water quality testing procedures. This method enables accurate and quantitative measurement of free chlorine concentrations. The findings reveal that the free chlorine content in all tested samples remains below the maximum permissible limit established by the Indonesian Ministry of Health, namely 0.1–0.5 mg/L. These results indicate that Megavin bottled drinking water is safe for consumption in terms of free chlorine levels and complies with the required safety standards.